(untitled) (Law Research Review Quarterly, 2026)
Sexual violence against children frequently occurs in Semarang, affecting not only the physical but also the psychological well-being of children. In response to the high number of cases of sexual violence against children in Semarang, Polrestabes Semarang as a law enforcement agency, is obligated to provide legal protection to victims. This article aims to analyze the implementation of legal protection for child victims of sexual violence at Polrestabes Semarang and the factors that lead to secondary victimization during the legal process at Polrestabes Semarang. This study uses victimology with a qualitative approach. Data collection techniques in this study were interviews, observation, and document study. Based on the research results, Polrestabes Semarang has implemented legal protection in a preventive and repressive manner. However, several obstacles are still found in its implementation, such as a lack of female investigators, limited psychologists, and cases that suddenly stop (stalled). In addition, child victims of sexual violence still experience secondary victimization during the investigation stage at Polrestabes Semarang, including repeated investigations, victim blaming by investigators, a lengthy legal process, and community stigma. Therefore, it can be concluded that Polrestabes Semarang has sought protection law for child victims of sexual violence, but in its implementation there are still obstacles found until secondary victimization practices towards the victim.